Analisis Kesalahan Penulisan Ejaan Pada Teks Negosiasi Siswa Kelas X Analis SMK Kesehatan Samarinda - Asyifa, Sarah; Sulistyowati, Endang Dwi; Elyana, Kukuh (Adjektiva: Educational Languages and Literature Studies, 2019)
This study aims were to describe the form of spelling errors, namely the form of letter errors, the form of word writing errors, the form of punctuation errors, and the form of writing errors of absorption elements in the negotiation texts by students of class X Analysts of Health Vocational High School Samarinda. The data was carried out by giving assignments to students for making negotiation texts and giving questions via google form. The data of this study amounted to 20 students negotiation texts. The spelling errors were analyzed by using PUEBI (General Guidelines for Indonesian Spelling) with qualitative descriptive analysis techniques. The results showed that there were still many spelling errors in the negotiation texts of student of class X Analysts of Health Vocational High School Samarinda. Spelling errors that found including errors in the use of letters consisting of errors in the use of capital letters and italics. Word writing errors included word combination errors, preposition errors, numbers and numbers writing errors, and pronoun writing errors. Errors in the use of punctuation marks included errors in the use of periods, errors in the use of commas, errors in the use of semicolons, errors in the use of question marks, errors in the use of exclamation points, errors in the use of quotation marks, and errors in the use of hyphens. Errors in writing absorption elements were not found in this study.